Photoacoustic tomography system for noninvasive real-time three-dimensional imaging of epilepsy - Wang, Bo (Optical Society of America, 2012)
A real-time three-dimensional (3D) photoacoustic imaging system was developed for epilepsy imaging in small animals. The system is based on a spherical array containing 192 transducers with a 5 MHz central frequency. The signals from the 192 transducers are amplified by 16 homemade preamplifier boards with 26 dB and multiplexed into a 64 channel data acquisition system. It can record a complete set of 3D data at a frame rate of 3.3 f/s, and the spatial resolution is about 0.2 mm. Phantom experiments were conducted to demonstrate the high imaging quality and real time imaging ability of the system. Finally, we tested the system on an acute epilepsy rat model, and the induced seizure focus was successfully detected using this system.